VIII INTERNATIONAL GOLDEN HORDE FORUM, BOLGHAR–KAZAN, JUNE 9–11, 2025 - Giniyatullina L.S. (Золотоордынское обозрение)
The VIII International Golden Horde Forum “Pax Tatarica: Medieval Sources and Historical Context” emerged as a landmark academic event in 2025, bringing together 151 researchers from 16 countries. The Forum served as a platform for in-depth discussions on current issues in the study of the Golden Horde, its role within the Eurasian historical landscape, military affairs, socio-political problems, and new approaches to analyzing written, archaeological, and numismatic sources. A notable extension of the Forum was the I International Summer School on the Golden Horde History, which provided a dynamic space for communication and education. This project successfully connected experienced scholars and early-career researchers in Turkic studies, medieval history, and source criticism, fostering a productive environment for scholarly exchange and collaboration. A significant politico-academic event held in parallel was the session of the Joint Working Group of Historians of Russia and Kazakhstan, which included participants from universities and research institutions, as well as representatives of executive and legislative authorities and diplomatic services. The newly presented research materials at the Forum offer promising prospects for a comprehensive study of various facets of the Golden Horde and Tatar khanates – from political and social developments to cultural and religious traditions. The Forum reaffirmed that the Golden Horde legacy remains a fertile ground for new discoveries, interdisciplinary research, and academic dialogue, both in the Russian Federation and near abroad.